2020
DOI: 10.1590/s2175-97902019000418365
|View full text |Cite
|
Sign up to set email alerts
|

A conglomeration of preclinical models related to myocardial infarction

Abstract: Cardiovascular diseases are the main source of death and morbidity in developed and developing nations. Animal models are required to propel our understanding of the pathogenesis, increase our knowledge, disease progress, and mechanism behind cardiovascular disorder, providing new approaches focused to improve the diagnostic and the treatment of these pathological conditions and additionally to test various therapeutic ways to deal with tissue regeneration and re-establish heart working following damage. A per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 72 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…A nomenclature was performed for all different experimental groups and the codes were written on the cages. Animals were fed with rodent specific pellet diet (Dayal animal feed) and normal drinking water ad libitum during this study [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A nomenclature was performed for all different experimental groups and the codes were written on the cages. Animals were fed with rodent specific pellet diet (Dayal animal feed) and normal drinking water ad libitum during this study [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Isoproterenol, produces highly cytotoxic free radicals which are used to stimulate peroxidation of membrane phospholipids leading to severe damage to the membrane of the myocardium resulting in an infarct-like necrosis of the cardiac tissue in experimental animal. ISO-induced myocardial necrosis establishes a well-standardized model for the reason that the pathophysiological changes in cardiac muscle of experimental animals are analogous to that perceived in human myocardial infarction or necrosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…CCl 4 is used as a chemical agent to induce myocardial infarction/cardiotoxicity. It mimics the pathology close to humans by producing free radicals, a rate-limiting process in cellular peroxidative damage [ 17 ]. These free radicals and other related oxidative species cause oxidative stress, which produces significant interrelated changes in cellular metabolism, thus increasing the calcium level inside the cell, which further causes damage to the permeability and transport of ions through the membrane and destroys the cells by LPO.…”
Section: Introductionmentioning
confidence: 99%
“…These free radicals and other related oxidative species cause oxidative stress, which produces significant interrelated changes in cellular metabolism, thus increasing the calcium level inside the cell, which further causes damage to the permeability and transport of ions through the membrane and destroys the cells by LPO. This model has been seen to elevate lactate dehydrogenase (LDH), creatine kinase (CK), and malondialdehyde (MDA) levels and alleviate the level of antioxidant enzyme armoury, which includes SOD, CAT, and GPx levels in the heart, indicating that the heart can be targeted by CCl 4 [ 17 , 18 ]. It has also been reported that the release of ROS can lead to myocardial ischaemia with subsequent cell injury and mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%